Spitz Nevus Arising upon a Congenital Glomuvenous Malformation. Issue 3 (3rd February 2012) - Arica, Deniz A.; Arica, Ibrahim E.; Yayli, Savas; Cobanoglu, Umit; Akay, Bengu N.; Anadolu, Rana; Bahadir, Sevgi
<x xml:space="preserve">Abstract</x> Abstract: There are several reports of the collision of vascular and pigmentary anomalies (e.g., phakomatosis pigmentovascularis) and the association between congenital melanocytic nevi and infantile hemangiomas. We report a case of Spitz nevus arising in skin overlying a congenital plaque‐like glomuvenous malformation (GVM). This is the first report of a Spitz nevus arising in direct contiguity to a GVM.